RESEARCH ON FACTORS AFFECTING THE EFFICIENCY OF SOLAR PHOTOPANELS - Safarov, Alisher; Rakhmatov, Obid (Innovatsion texnologiyalar, 2024)
The use of solar photovoltaic devices is becoming increasingly important in stabilizing energy security and solving environmental problems. Particular attention is paid to the scientific substantiation of factors affecting the efficiency of solar photovoltaic devices in a continental changing climate. Assessing the possibilities of using solar photovoltaic devices in the climatic conditions of Uzbekistan and increasing their efficiency is one of the most pressing scientific and technical tasks. Mathematical models of the dependence of the efficiency of solar photovoltaic devices on solar radiation, external temperature, wind speed and the amount of dust on the surface of solar panels are presented. The simulation is performed in Matlab/Simulink. It has been studied that the power of a photopanel is a maximum of 200 W at an outside temperature of 25 oC and solar radiation of 1000 W/m2 , and at a temperature of 75 oC the output power is approximately 110 W. When the amount of dust on the surface of solar photo panels is about 0.1 g/m2 , the device efficiency is a maximum of 16%, and at 80 g/m2 the device efficiency decreases to 4%. It was found that the temperature of solar photovoltaic panels is 72 oC at a very low wind speed, and the temperature difference is 48 oC at a wind speed of 25 m/s. It is based on the fact that the energy efficiency of solar photovoltaic devices can be increased by 20-30% by cleaning the surface of solar panels from dust and preserving their heat in changing climatic conditions